Estudo sobre relatórios de estágio supervisionados em cursos de licenciatura em letras: uma reflexão sobre a formação inicial do professor de espanhol - Curti, Natália (Universidade Federal de São Carlos, 2015)
This research, of an interpretive and documentary nature, aims to analyze the reports that are produced by undergraduates of a Portuguese-Spanish Language Teaching Course, as a requirement for the subject Supervised Practicum in Foreign Language (observation and practice stages). The corpus of this study consists of reports written by undergraduates as part of the subject Supervised Practicum in Foreign Language of Portuguese-Spanish Language Teaching Courses in two universities in São Paulo State, a public one and a private one. The organization and analyses of data were done according to the analyses of categories (BURNS, 1999). As a theoretical background, we considered authors such as: Almeida Filho (1993; 1999; 2006; 2011); Alvares-Ortís (2006); Vieira-Abrahão (2001; 2002; 2006; 2007); Silva & Margonari (2005); Kfouri-Kaneoya (2003, 2008); Gileno (2013), among others. We assumed that the undergraduates of the Portuguese-Spanish Language Teaching Courses, when observing and teaching classes in regular schools, reflect on some aspects related to the language teaching/learning process (teacher, student, language skills, types of exercises, the content of classes, etc.) and describe their reflections and experiences in the reports they write by the end of the subject Supervised Practicum. Thus, by means of the reports written by the undergraduates, we sought the aspects that could support the following research questions: 1- What do undergraduates reveal in the reports they produce during the Supervised Practicum (observation and practice stages)? 2- Do the reports on the practice stage of Supervised Practicum indicate a consistent practice with the reflections made in the reports on the observation stage of Supervised Practicum? 3- Are there moments of theoretical and methodological reflection on the observation and the practice in the reports that relate to the studies of Applied Linguistics? When answering the research questions, despite consulting several theoretical texts, we noted in the reports that there are several problems in the stages of the Supervised Practicum that are not addressed in the publications consulted, such as the carelessness of some higher education institutions concerning the initial education of teachers and the difficulty of finding schools where the undergraduates are able to carry out the Supervised Practicum of some foreign languages, including Spanish. We also noticed that, depending on the institution, there are notable differences on how to conduct and record the Supervised Practicum stages, and that the expected reflection about the theoretical and methodological aspects, although not fully developed in all reports, can be perceived in some of them. Therefore, we tried to point out and justify the failures of the Supervised Practicum stages that we found in our corpus of research in order to contribute to the improvement in Supervised Practicum and hence to teacher education.

Esta investigación interpretativista y documental, analiza informes producidos por estudiantes brasileños de la carrera de Profesorado en Español como Lengua Extranjera durante su pasantía obligatoria, en la que realizan actividades de observación y práctica docente (asignatura: “Estágio Supervisionado de Língua Estrangeira”). La fundamentación teórica que ha direccionado esta investigación se basa en los estudios de Almeida Filho (1993; 1999; 2006; 2011); Alvares-Ortís (2006); Vieira-Abrahão (2001; 2002; 2006; 2007); Silva & Margonari (2005); Kfouri-Kaneoya (2003; 2008); Gileno (2013), entre otros. El corpus está formado por los informes recogidos en dos instituciones de enseñanza superior, una pública y otra privada, ubicadas en el interior del Estado de São Paulo (Brasil). La organización de los datos se hizo a través del análisis de categorías, basado en Burns (1999). A través de las informaciones obtenidas, se buscó contestar las siguientes preguntas de investigación: 1. ¿Qué revelan los estudiantes en los documentos producidos durante la pasantía obligatoria de observación y práctica docente? 2- ¿Los informes de las prácticas de regencia indican una práctica coherente con las reflexiones formuladas en los informes de pasantía de observación? 3- ¿Hay momentos de reflexión teórica y metodológica sobre la observación y la práctica en los informes que se conecten con los estudios de la Lingüística Aplicada?
Keywords: Professores - formação inicial; Estágio supervisionado; Língua espanhola - ensino; Supervised Practicum; Spanish Language Teaching/Learning; Initial Spanish Teacher Education; Pasantía; Enseñanza/Aprendizaje de lengua española; Formación inicial de profesores de español; LINGUISTICA, LETRAS E ARTES::LINGUISTICA